An examination of a novel multipanel of CSF biomarkers in the Alzheimer's disease clinical and pathological continuum. Issue 3 (18th December 2020) - Van Hulle, Carol; Jonaitis, Erin M.; Betthauser, Tobey J.; Batrla, Richard; Wild, Norbert; Kollmorgen, Gwendlyn; Andreasson, Ulf; Okonkwo, Ozioma; Bendlin, Barbara B.; Asthana, Sanjay; Carlsson, Cynthia M.; Johnson, Sterling C.; et al.
Abstract: Introduction: This study examines the utility of a multipanel of cerebrospinal fluid (CSF) biomarkers complementing Alzheimer's disease (AD) biomarkers in a clinical research sample. We compared biomarkers across groups defined by clinical diagnosis and pTau181 /Aβ42 status (+/−) and explored their value in predicting cognition. Methods: CSF biomarkers amyloid beta (Aβ)42, pTau181, tTau, Aβ40, neurogranin, neurofilament light (NfL), α‐synuclein, glial fibrillary acidic protein (GFAP), chitinase‐3‐like protein 1 (YKL‐40), soluble triggering receptor expressed on myeloid cells 2 (sTREM2), S100 calcium binding protein B (S100B), and interleukin 6 (IL6), were measured with the NeuroToolKit (NTK) for 720 adults ages 40 to 93 years (mean age = 63.9 years, standard deviation [SD] = 9.0; 50 with dementia; 54 with mild cognitive impairment [MCI], 616 unimpaired). Results: Neurodegeneration and glial activation biomarkers were elevated in pTau181 /Aβ42 + MCI/dementia participants relative to all pTau181 /Aβ42 ‐ participants. Neurodegeneration biomarkers increased with clinical severity among pTau181 /Aβ42 + participants and predicted worse cognitive performance. Glial activation biomarkers were unrelated to cognitive performance. Discussion: The NTK contains promising markers that improve the pathophysiological characterization of AD. Neurodegeneration biomarkers beyond tTau improved statistical prediction of cognition and disease stages.